Human Milk and Donkey Milk, Compared to Cow Milk, Reduce Inflammatory Mediators and Modulate Glucose and Lipid Metabolism, Acting on Mitochondrial Function and Oleylethanolamide Levels in Rat Skeletal Muscle - Trinchese, Giovanna; Cavaliere, Gina; De Filippo, Chiara; Aceto, Serena; Prisco, Marina; Chun, Jong Tai; Penna, Eduardo; Negri, Rossella; Muredda, Laura; Demurtas, Andrea; Banni, Sebastiano; Berni-Canani, Roberto; et al. (Frontiers in Physiology, 2018)
Scope: Milk from various species differs in nutrient composition. In particular, human milk (HM) and donkey milk (DM) are characterised by a relative high level of triacylglycerol enriched in palmitic acid in sn-2 position. These dietary fats seem to exert beneficial nutritional properties through N-acylethanolamine tissue modulation. The aim of this study is to compare the effects of cow milk (CM), DM, and HM on inflammation and glucose and lipid metabolism, focusing on mitochondrial function, efficiency and dynamics in skeletal muscle, which is the major determinant of resting metabolic rate. Moreover, we also evaluated the levels of endocannabinoids and N-acylethanolamines in liver and skeletal muscle, since tissue fatty acid profiles can be modulated by nutrient intervention. Procedures: To this aim, rats were fed with CM, DM or HM for 4 weeks. Then, glucose tolerance and insulin resistance were analyzed. Pro-inflammatory and anti-inflammatory cytokines were evaluated in serum and skeletal muscle. Skeletal muscle was also processed to estimate mitochondrial function, efficiency and dynamics, oxidative stress, and antioxidant/detoxifying enzyme activities. Fatty acid profiles, endocannabinoids and N-acylethanolamine congeners were determined in liver and skeletal muscle tissue. Results: We demonstrated that DM or HM administration reducing inflammation status, improves glucose disposal and insulin resistance and reduces lipid accumulation in skeletal muscle. Moreover, HM or DM administration increases redox status, and mitochondrial uncoupling, affecting mitochondrial dynamics in the skeletal muscle. Interestingly, HM and DM supplementation increase liver and muscle levels of the N-oleoylethanolamine (OEA), a key regulator of lipid metabolism and inflammation. Conclusions: HM and DM have a healthy nutritional effect, acting on inflammatory factors and glucose and lipid metabolism. This beneficial effect is associated to a modulation of mitochondrial function, efficiency and dynamics and to an increase of OEA levels in skeletal muscle.